2009
DOI: 10.1177/0363546509332497
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Concussion History and Gender in Recovery from Soccer-Related Concussion

Abstract: A history of concussion and gender may account for significant differences in postconcussive neurocognitive test scores in soccer players and may play a role in determining recovery. These differences do not appear to reflect differences in mass between genders and may be related to other gender-specific factors that deserve further study.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
88
1
2

Year Published

2011
2011
2020
2020

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 283 publications
(104 citation statements)
references
References 33 publications
9
88
1
2
Order By: Relevance
“…11,38,39 Even though previous studies have shown fewer than three prior concussions to not predispose patients to prolonged symptoms, 40 recent data have begun to indicate poorer performance on neurocognitive testing in patients with only one prior injury. 41 Our data show patients with at least two prior concussions may be predisposed to poorer outcomes.…”
Section: Discussionmentioning
confidence: 60%
“…11,38,39 Even though previous studies have shown fewer than three prior concussions to not predispose patients to prolonged symptoms, 40 recent data have begun to indicate poorer performance on neurocognitive testing in patients with only one prior injury. 41 Our data show patients with at least two prior concussions may be predisposed to poorer outcomes.…”
Section: Discussionmentioning
confidence: 60%
“…This gender bias in sampling likely results from the higher prevalence of mTBI among males ; however, when matched by sport, females present a higher rate of mTBI than the opposite gender (Gessel et al, 2007), which presents the importance of expanding mTBI research across more representative samples. Although not exhaustive, individual studies have presented disparate results in relation to cognitive outcomes of mTBI (e.g., minor female advantages, Moore, Ashman, Cantor, Krinick, & Spielman, 2010; minor male advantages, Colvin et al, 2009; no long-term differences, Tsushima, Lum, & Geling, 2009). One meta-analysis assessed gender as a moderator (Dougan et al, 2013); however, their review involved effect sizes on neuropsychological outcomes at only 1-10 days post-mTBI.…”
Section: Unexplored Moderating Variablesmentioning
confidence: 99%
“…Female athletes have greater concussion rates, report greater increases in symptoms after concussion, and have greater impairment on neuropsychological testing after concussion compared with male athletes. It is unclear if these differences are biomechanical, hormonal and/or are due to reporting bias [6366]. In CTE, the vast majority of patients studied have been men because brain donation has largely occurred among professional athletes in contact sports.…”
Section: Epidemiologymentioning
confidence: 99%